2019
DOI: 10.1519/jsc.0000000000001954
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Six Consecutive Days of Sprint Training in Hypoxia on Performance in Competitive Sprint Runners

Abstract: The purpose of the present study was to determine the effects of 6 successive days of repeated sprint training in moderate hypoxia on anaerobic capacity in 100-200-m sprint runners. Eighteen male sprint runners (age, 20.0 ± 0.3 years; height, 175.9 ± 1.1 cm; body mass, 65.0 ± 1.2 kg) performed repeated cycling sprints for 6 consecutive days in either normoxic (NOR; fraction of inspired oxygen [FiO2], 20.9%; n = 9) or hypoxic conditions (HYPO; FiO2, 14.5%; n = 9). The repeated sprint ability (10 × 6-s sprints),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…These findings are consistent with a recent publication that reported a significant improvement in 7-s maximal sprint performance after four weeks of RSH in female team-sport athletes [25]. Moreover, we recently demonstrated that 6 successive days of RSH significantly improved the running time of the initial phase of 60-m sprint, with a concomitant increase in muscle PCr content, although the sample size was relatively small [26]. Therefore, we hypothesized that the increase in maximal power output in the HYPO group may be associated with augmented muscle PCr content.…”
Section: Performance Adaptationssupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with a recent publication that reported a significant improvement in 7-s maximal sprint performance after four weeks of RSH in female team-sport athletes [25]. Moreover, we recently demonstrated that 6 successive days of RSH significantly improved the running time of the initial phase of 60-m sprint, with a concomitant increase in muscle PCr content, although the sample size was relatively small [26]. Therefore, we hypothesized that the increase in maximal power output in the HYPO group may be associated with augmented muscle PCr content.…”
Section: Performance Adaptationssupporting
confidence: 93%
“…Therefore, consecutive days of repeated sprint training over a short period may be a potential stimulus for increasing brief power output and muscle PCr content. More recently, we found that 6 consecutive days of RSH significantly increased muscle PCr content (18.4-39.6 % increase) in competitive sprinters, although the finding was not conclusive due to the relatively small sample size (n = 6) [26].…”
Section: Introductionmentioning
confidence: 78%
“…Faiss et al (2015) reported that 6 sessions of RSH improved exercise performance, compared to RSN 7) . Moreover, Kasai et al (2019) reported that 6 consecutive days of RSH improved exercise performance (improved repeated 10-sec sprint ability) and evoked physiological adaptation (increased phosphocreatine [PCr] content) 8) . Therefore, 6 consecutive days (6 sessions) of RSH seems to be enough to improve exercise performance and evoke physiological adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…One previous study reported that performance during a single Wingate effort improved when assessed 9 days but not 2 days after the hypoxic training intervention (Hendriksen and Meeuwsen, 2003). Two other studies using trained sprinters reported that 5 to 6 consecutive days of hypoxic training composed of RW (repeated maximal sprints of 15-30 s) and repeated sprint training (repeated maximal 6-s sprints) failed to induce improvement in single Wingate effort 3 days after the intervention (Kasai et al, 2017(Kasai et al, , 2019. Since performance was not assessed in the first few days or several weeks after the intervention, immediate and long-term consequences of our intervention are unknown.…”
Section: Performance Outcomesmentioning
confidence: 99%
“…Although 100-or 200m race times are clearly shorter than 30 s, it is common for these athletes to perform workouts of this duration during their preparation phase. Practically, one study showed that 6-to 20s repeated sprint cycling training in hypoxia improved 60-m sprinting performance in 100-200 m sprint runners, with these effects being mainly visible for the 0-10 m distance interval (Kasai et al, 2019). Moreover, efforts were performed on a cycle ergometer during this period of training in order to minimize ground contacts and the possibly of sustaining an injury since 6 sessions were planned over a 2-wks period.…”
Section: Additional Considerations and Limitationsmentioning
confidence: 99%